Features of cystitis management in outpatient therapeutic practic - D. S. Sukhanov; V. A. Filippovich; Yu. S. Alexeeva; E. V. Timofeev (Лечащий Врач, 2024)
Background. Cystitis is one of the most common urinary tract infections undergoing treatment on an outpatient basis. In Russia, up to 36 million cases of the disease are registered annually. The main causative agent of uncomplicated cystitis, detected in 75% of cases, is E. coli, in the remaining cases, the etiological agents are S. saprophyticus, Klebsiella spp. and a number of enterobacteria, extremely rare – anaerobic microorganisms, chlamydia and ureaplasma. The article discusses predisposing factors and the pathogenesis of acute uncomplicated cystitis.Results. The aim of treatment of acute uncomplicated cystitis is rapid eradication of the pathogen, leading to clinical and microbiological recovery, as well as prevention of relapses of the disease. Uncomplicated acute cystitis in most cases is treated in outpatient settings. The basis of pharmacotherapy of acute cystitis is antibacterial drugs. The appointment of an antibacterial drug is carried out empirically when the symptoms of the disease are detected, taking into account the alleged etiology of cystitis and the clinical and pharmacological characteristics of the drug, with mandatory consideration of the current state of antibiotic resistance. The optimal choice of the drug and the antibiotic therapy regimen contributes to a faster recovery and a reduction in the risk of chronic disease.Conclusion. Detailed information about the existing regimens of antibiotic therapy for acute cystitis is presented in the article, as well as the main indications for the appointment of antibacterial drugs. The results of studies on the effectiveness of the drug cefixime in the treatment of acute uncomplicated cystitis, including the cystitis of pregnant women, are analyzed.